Contribuições ao estudo do clima em serviços: um estudo de caso no setor hoteleiro a partir da perspectiva da linha de frente - Machado, Maria Julieta Cherulli (2001)
This is an exploratory qualitative research, carried out in lhe service area, about the service climate theme. The dissertation which consists of a bibliographical review and a field research, contributes to the framework of the understanding about the necessary conditions to establish a propitious climate to the offer of services by an organization. The dissertation is a diagnosis that, through a case study carried out in a brazilian company, focuses the frontline's perception about service climate aspects, showing the most important ones which, according to the frontline's opinion, affect their job satisfaction. The dissertation identifies perception deviations by companng the frontline's perspective to the supervision's perspective. This dissertation can be useful for service organizations because it signalizes improvement opportunities concerning lhe fulfillment of the frontline employee' s needs. The study identifies the aspects of the service climate taken as positive factors and those taken as negative factors by the frontline employees. The study proposes a composition of the service climate aspects produced from the research results.